SPE Production Operations Symposium 1993
DOI: 10.2118/25464-ms
|View full text |Cite
|
Sign up to set email alerts
|

Refracturing: Observations and Theories

Abstract: Treating pressures from refracturing treatments and simulations of horizontal stress changes due to production suggest that the initiation of the refracture plane will be normal to that of the initial treatment. This possibility makes more wells candidates for refracturing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(35 citation statements)
references
References 8 publications
2
33
0
Order By: Relevance
“…The refracture reorientation theory presented by EIbel and Mack in Ref. 3 is that pore pressure depletion around a propped fracture treatment is elliptical in profile ( Figure 1) and, therefore, reduces the maximum horizontal stress by a greater amount than it reduces the minimum horizontal stress. If the difference in the stress reduction is greater than the original horizontal stress bias (max.…”
Section: Reorientation Mechanismsmentioning
confidence: 94%
See 1 more Smart Citation
“…The refracture reorientation theory presented by EIbel and Mack in Ref. 3 is that pore pressure depletion around a propped fracture treatment is elliptical in profile ( Figure 1) and, therefore, reduces the maximum horizontal stress by a greater amount than it reduces the minimum horizontal stress. If the difference in the stress reduction is greater than the original horizontal stress bias (max.…”
Section: Reorientation Mechanismsmentioning
confidence: 94%
“…3, but the angle of reorientation may be significantly different due to a very asymmetric depletion of the pore pressure around the initial propped fracture plane. Asymmetric reservoir depletion may result from local reservoir faults, boundaries, or other heterogeneities.…”
Section: Planviewmentioning
confidence: 99%
“…For such kind of wells, refracturing can reopen the existing perforations and fracture network to revitalize the productivity (Elbel and Mack 1993). In the case of formation damage, it can reopen the existing fracture networks and restore the fracture conductivity to the wellbore, which is known as ''reconnect'' treatment strategy.…”
Section: Simulation Of Refracturingmentioning
confidence: 99%
“…Refracturing has been employed as a method for increasing production rates and/or economic recoverable reserves since the advent of hydraulic fracturing. Several authors have suggested criteria for refracturing candidate selection (Coulter and Menzie 1973;Crowell and Jennings 1978;Conway et al 1985;Elbel and Mack 1993;Reese et al 1994). Typical candidates for refracturing, from a reservoir engineering perspective, are wells with little fracture penetration and/or poor or degrading fracture conductivity, provided that adequate reserves are in place.…”
Section: Case Studymentioning
confidence: 99%